Սփյուռքագիտության արդի հիմնախնդիրները - Հակոբյան, Հրանուշ (YSU Journal of International Affairs, 2016)
The article analyzes the main features of the new role of Diaspora in political science, Diaspora studies, and why not, cooperation with international organizations. The prospects of development of the diaspora, the role and importance of Diaspora studies, as a new branch in the sciences and in this context the approaches and definitions of the term "diaspora" put forward by various scientists.
Keywords: Diaspora, Homeland, identity, challenge, immigration, migration, international organizations